(untitled) (KASBIT Business Journal, 2020)
This article will determine the character and scope of the development process of the Sindh Public Sector Organization Strategy Planning. Such analysis consists of the formation of the strategic plan process and impact of external/internal factors due to which distraction occurs in the development of the strategic plan process & estimating the quality of the strategic plan. Furthermore, the purpose of the research will move on to estimate the pressure of the Public Sector in the development of the Strategic Planning Process. The research structure includes all variables which also include hypothesized variable relationships among them. A questionnaire survey was done by an email in this research, which is considered a suitable method related to this research. From 40 public sector organizations and 110 private sectors all together 450 surveys were conducted. The result of this survey data supports the research structure of the thesis. The research identifies the logical structure to connect the public sector organization strategic planning (SP) procedures with the consistent variables. Such finding leads to the repercussion contribution, to the management of Sindh Public Sector, Pakistan & to some extent in the Public Sector of Africa and Central Asian region. The findings also recommend that circle of research should also extend to the African and Central Asian countries, so that the relation among them concerning economic, financial, and managerial can be advantageous, especially in Public Sector Organisations. It is suggested that researchers can examine the procedure of Public Sector Strategic Planning (SP) implementation in the Federal-Provincial Government of Pakistan.